2022
DOI: 10.3389/fnmol.2022.917598
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Mediates Hippocampal Damage and Aberrant Neurogenesis Contributing to Epilepsy-Associated Anxiety

Abstract: Anxiety disorder is one of the most common comorbidities in temporal lobe epilepsy (TLE), but its neurobiological mechanisms remain unclear. Here we identified a novel target, interleukin-17A (IL-17A), which can contribute to TLE-associated anxiety. Epileptic seizures were induced in 6-week-old IL-17A wild-type (WT) and knockout (KO) mice by pilocarpine injection. To evaluate anxiety level, we subjected mice to open field and elevated plus maze (EPM) tests and measured the time animals spent in center zone or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The reaction was terminated by 0.05 M trizma buffer and sections were mounted with dibutylphthalate polystyrene xylene (DPX), and observed under a light microscope (Olympus, Tokyo, Japan, BX51). For the evaluation of SE-induced neuronal death, Fluoro-Jade B (FJB) staining was performed ( Choi et al, 2022 ). Slides with coronal hippocampal sections were placed in 0.06% KMnO4 solution for 7 min, followed by the incubation in 0.001% FJB (Biosensis, Thebarton, Australia, TR-150-FJB) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was terminated by 0.05 M trizma buffer and sections were mounted with dibutylphthalate polystyrene xylene (DPX), and observed under a light microscope (Olympus, Tokyo, Japan, BX51). For the evaluation of SE-induced neuronal death, Fluoro-Jade B (FJB) staining was performed ( Choi et al, 2022 ). Slides with coronal hippocampal sections were placed in 0.06% KMnO4 solution for 7 min, followed by the incubation in 0.001% FJB (Biosensis, Thebarton, Australia, TR-150-FJB) for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…FJB-positive or immunoreactive cells were quantified as previously described ( Choi et al, 2022 ). The number of FJB-positive cells was counted in every 12th hippocampal section, which was summed up and multiplied by 24 to estimate the total number of FJB-expressing cells in an animal.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have linked the IL-17A and IL-23A pathways to anxiety and depression in both human subjects and animal models 33 38 . Preclinical research on mice indicates that IL-17A significantly contributes to the development of anxiety associated with epilepsy, stroke, or chronic stress 39 41 . Consistent with these findings obtained from animal model studies, IL-17A serum levels were found to be positively and independently correlated with the anxiety severity in rheumatoid arthritis patients even after adjustment for disease activity for arthritis and pain 42 .…”
Section: Introductionmentioning
confidence: 99%